Human interdependency for sustainable well-being: structural invariance across settlement areas - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Hitam, Mizan; Abdullah, Alias (Malaysia Institute of Planner, 2018)
This survey research examined the underlying structure of subjective sustainable well-being (SSWB) discovered in the relationships of (i) Human Interdependence with other Humans (HIH), (ii) Human Interdependence with the Environment (HIE), and (iii) subjective well-being (SWB). The objectives of the empirical analysis were (i) to assess the causal relationship between human interdependence and SWB which instituted the SSWB structural model, and (ii) to evaluate the settlement areas-invariant of the causal structure of SSWB. The data was collected from self-reported questionnaires administered to 4315 working Malaysians. The findings of the structural equation modelling supported the adequacy of SSWB. The results also found that settlement areas, in particular the urban, sub-urban and rural areas, appeared to moderate the structural relationships of SSWB.